2009
DOI: 10.1001/archinternmed.2009.255
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Implantable Cardioverter-Defibrillators for the Primary Prevention of Sudden Cardiac Death in Women With Advanced Heart Failure

Abstract: Implantable cardioverter-defibrillator therapy for the primary prevention of sudden cardiac death in women does not reduce all-cause mortality. Further studies are needed to investigate the reasons for this ob servation and to define the population of women who may benefit most from implantable cardioverter-defibrillator therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(127 citation statements)
references
References 47 publications
4
120
0
3
Order By: Relevance
“…Similar findings were reported in 2 other meta-analyses. 2,3 Although the results of these studies require prospective validation, our analysis suggests that women are less likely to die suddenly and therefore have less opportunity to benefit from an ICD.…”
Section: Discussionmentioning
confidence: 88%
“…Similar findings were reported in 2 other meta-analyses. 2,3 Although the results of these studies require prospective validation, our analysis suggests that women are less likely to die suddenly and therefore have less opportunity to benefit from an ICD.…”
Section: Discussionmentioning
confidence: 88%
“…In a meta-analysis of 5 major randomized primary prevention trials comparing medical therapy with ICD therapy, Ghanbari et al 72 reported that ICD did not confer a survival benefit for women (HR, 1.01; 95% CI, 0.76-1.33; P=0.95). In contrast, a 22% reduction in mortality was observed for men receiving ICD therapy (HR, 0.78; 95% CI, 0.70-0.87; P<0.001).…”
Section: Primary and Secondary Prevention Of Scdmentioning
confidence: 99%
“…Data from a sample of Medicare beneficiaries who met the criteria for ICD implantation for the primary prevention of SCD revealed that only 8.6/1000 women received an ICD compared with 32.3/1000 men within 1 year of diagnosis. 33 An observational study of more than 13 000 patients admitted with systolic heart failure (LVEF <30%) to hospitals participating in the American Heart Association's Get With the Guidelines-Heart Failure program reported that, among patients eligible for ICD therapy, only 35.4% of them had an ICD or a planned ICD implantation upon discharge. After adjustment for patient characteristics and hospital factors, the adjusted odds of ICD use were 0.73 for African American men, 0.62 for Caucasian women, and 0.56 for African American women, compared with Caucasian men.…”
Section: Sex Differences In Utilization and Response To Implantable Dmentioning
confidence: 99%